The Role of Teachers in Developing Memorization Skills of Students in Talented and Regular Classes at RA Al-Munawwarah Pamekasan - Samsul Arifin; Ramli Ramli (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe and analyze the role of teachers in developing the Qur'an reading skills of students in both the talent and regular classes at RA Al-Munawwarah Pamekasan. The background of the research is the varying levels of students’ abilities in reading the Qur'an at an early age, which led the school to group students into talent and regular classes. In this context, teachers play a crucial role in adapting instructional strategies to suit the needs and abilities of each student group. This research employed a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with teachers, and documentation of teaching and learning activities. The results revealed that teachers in the talent class focused more on improving tajweed, reading fluency, and memorization through individualized approaches and the talaqqi method. In contrast, teachers in the regular class concentrated on introducing the Arabic alphabet and basic Qur’anic reading skills using the Iqra’ method, songs, and educational games. The difference in teacher roles between the two classes was adjusted according to students’ initial abilities. Supporting factors included professional teacher competence, parental support, and a conducive learning environment. Inhibiting factors included limited instructional time and varying student abilities within the same class. In conclusion, the teacher's role is essential and significantly influences the gradual and targeted development of students' Qur’an reading skills in both the talent and regular classes.